Edukasi Penerapan Protokol Kesehatan COVID-19 Di SMAN Titian Teras Abdurrahman Sayoeti Kabupaten Muara Jambi - M.Ridwan M.Ridwan; Puspita Sari; M. Dody Izhar (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
The spread of Coronavirus disease (COVID-19) is currently increasing, and it is very easy for transmission to occur, especially in an environment that is a center for gatherings. During this pandemic, schools are encouraged to do online learning, but there are some schools that are allowed to do face-to-face learning, one of which is SMA Titian Teras. This becomes very risky for an increase in the transmission of the Covid-19 virus in schools. Efforts that can be made to overcome this are education about the application of the COVID-19 health protocol. This education aims to increase knowledge and practice for teachers, educators, and students at Titian Teras High School in preventing the spread of the Covid-19 disease. This service is carried out at Titian Teras High School with a target number of 20 teachers/students/educational staff offline. This service activity was carried out by 3 lecturers and 5 students.